A Philosophical Study of Peace Counseling from Cognitive Behavioral, Multicultural, Spiritual, and Humanistic Paradigms - Nurlita Hendiani; Akhmad Fajar Prasetya; Agus Supriyanto (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
The quality of life of individuals and groups plays an important role in building harmonious social relationships through the principles of peace psychology implemented in peace education and realized in peace counseling. However, most peace counseling models still focus on technical and practical aspects, while their ontological, epistemological, and axiological philosophical foundations have not been studied in depth. This theoretical gap has the potential to weaken the scientific foundation and direction of peace counseling intervention development. Therefore, this study aims to examine various peace counseling models from a philosophical perspective as a basis for strengthening counseling theory and practice. The research method used is a literature study of books and journal articles related to peace counseling published between 2019–2025. Data analysis was conducted using qualitative analysis techniques through data reduction, data presentation, and conclusion drawing. The results of the study show that the peace counseling model developed by experts is based on four main counseling philosophies: humanistic, cognitive-behavioral, spiritual, and multicultural. Ontologically, humans are understood as religious, rational, social, and cultural beings who have the potential for both conflict and peace. Epistemologically, knowledge about peace is built through the integration of cognitive-behavioral change, self-awareness, spiritual values, and local wisdom. Axiologically, peace counseling is oriented towards the formation of peaceful, tolerant, compassionate individuals who are capable of building social harmony. Although this philosophy has not been fully studied by model developers, this novelty reveals that spiritual philosophy can be integrated with all guidance and counseling philosophies. Therefore, it is hoped that in the future, counseling model developers will pay attention to philosophical studies as the root of theory and practice.